Victoria Christman, Pragmatic Toleration. The Politics of Religious Heterodoxy in Early Reformation Antwerp, 1515-1555. Changing Perspectives on Early Modern Europe - Violet Soen (BMGN: Low Countries Historical Review, 2016)
Victoria Christman, Pragmatic Toleration. The Politics of Religious Heterodoxy in Early Reformation Antwerp, 1515-1555. Changing Perspectives on Early Modern Europe (Rochester NY: University of Rochester Press, 2015, viii + 241 pp., isbn 978 1 58046 516 8).